Evaluation of antioxidant capacity and antifungal activity of the total ethanolic extract and fractions from teloschistes exilis (Michx.) vain. (2019)
Teloschistes exilis (Michx.) Vain is an underexplored lichen. In the last decades, there has been a growing interest for the study of lichenic biodiversity, as a source of new natural products, because these produce potential secondary metabolites for pharmacological and industrial uses, highlighting their antioxidant and antifungal properties. For that reason, this study evaluated the antioxidant capacity with 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical (ABTS*+ assay) and the antifungal activity of the total ethanolic extract (EtOH) and different polarity fractions from Teloschistes exilis (Michx.) Vain against Penicillium digitatum and Aspergillus niger using disk diffusion technique. According to antioxidant activity, the best-obtained value was for the EtOH with 37.58 mg/L MeOH, with ascorbic acid. In terms of antifungal activity, for equivalent sensitivity, against Penicillium digitatum, for each mg of ketoconazole, 213.4 mg of Petroleum ether fraction were required, while for each mg of fluconazole, 228.3 mg of Petroleum ether fraction were required. Regarding to antifungal activity against Aspergillus niger, for each mg of ketoconazole, 465.6 mg of Petroleum ether fraction are required, while for each mg of fluconazole, 174.6 mg of Petroleum ether fraction are needed. The highest polarity solvents have a better relative antioxidant activity in relation with standard solutions, whereas susceptibility tests applied for Aspergillus niger and Penicillium digitatum showed the best antifungal activity for the low polarity fraction of Petroleum ether for both controls. Considering that are fractions, the antioxidant and antifungal potential of Teloschistes exilis (Michx.) Vain should be elucidated in posterior studies.